Ultrasound-guided gluteal nerves electrical stimulation to enhance strength and power in individuals with chronic knee pain: a randomized controlled pilot trial - Sartori, Francesco; Fagnani, Pedro Luiz Flores; Monne-Guasch, Laia; La Cagnina, Giovanni; Picañol, Javier; Puig-Diví, Albert (Frontiers in Medicine, 2024)
Introduction Various pathophysiological contexts can be accompanied by weakness, arthrogenic muscle inhibition, and even disability. In this scenario, peripheral nerve stimulation has been studied not only for pain management but also for the improvement of neuromuscular parameters. For this purpose, the use of Transcutaneous Electrical Nerve Stimulation (TENS) has typically been investigated, but recently, the use of ultrasound-guided percutaneous peripheral nerve stimulation (pPNS) has gained popularity. In this regard, electrical stimulation has a predisposition to activate Type II muscle fibers and has been shown to be capable of generating short-term potentiation by increasing calcium sensitivity. However, the evidence of pPNS applied in humans investigating such variables is rather limited. Objectives This pilot study aimed to assess the feasibility of the methodology and explore the potential of pPNS in enhancing hip extension performance in individuals suffering from knee pain, comparing it with TENS. Methods Twelve participants were divided into pPNS and TENS groups, undergoing pre- and post-intervention assessments of peak concentric power (W), strength (N), execution speed (m/s), and one-repetition maximum (1RM) (kg) estimation. For pPNS, two needles were positioned adjacent to the superior and inferior gluteal nerves under ultrasound guidance. For TENS, electrodes were positioned between the posterosuperior iliac spine and the ischial tuberosity, and halfway between the posterosuperior iliac spine and the greater trochanter. The interventions consisted of 10 stimulations of 10 s at a frequency of 10 Hz with a pulse width of 240 μs, with rest intervals of 10 s between stimulations. Results Peripheral nerve stimulation significantly improved concentric power at 30% (p = 0.03) and 50% (p = 0.03) of 1RM, surpassing TENS, which showed minimal changes. No significant strength differences were observed post-intervention in either group. Conclusion This work presents evidence where pPNS applied to the gluteal nerves results in an enhanced performance of hip extension at submaximal loads. However, this improvement does not seem to be reflected in short-term changes in the estimation of the 1RM by the force-velocity profile.